(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
Physical education plays an important role in the holistic development of students in general education. However, organizing meaningful and interesting physical education classes can be difficult for teachers for time, resources, and other limitations common in school settings. This article aims to discuss some effective strategies and approaches to organizing quality physical education classes in primary and secondary schools.